2006
DOI: 10.1590/s1519-69842006000500015
|View full text |Cite
|
Sign up to set email alerts
|

Spiders of soybean crops in Santa Fe province, Argentina: influence of surrounding spontaneous vegetation on lot colonization

Abstract: Trials during two consecutive soybean cycles were performed in central Santa Fe in order to determine the main spider families present in the crop and to determine the influence of spontaneous margin flora on colonization towards the lot. Samplings were done by sweeping net and pitfall traps. It was concluded that:1. Oxyopidae was the most frequent family in the herbaceous layer of both the margins and the soybean crop, and Lycosidae in the lower layer; 2. Margin strips in a soybean lot contribute to the colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
22

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 20 publications
2
8
0
22
Order By: Relevance
“…These families coincided partially with those recorded in crops of soybeans, alfalfa, wheat and cotton (Liljesthröm et al, 2002;Beltramo et al, 2006;Armendano & González, 2009Almada et al, 2012, respectively), where Anyphaenidae, Salticidae and Linyphiidae were the main families in terms of their abundance. These families are also represented with greater abundance in livestock systems (Toti et al, 2000;Warui et al, 2005), as well as in reserves and national parks (Corronca & Abdala, 1994;Rubio et al, 2004;Grismado, 2007;Avalos et al, 2009;Rubio, 2015).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These families coincided partially with those recorded in crops of soybeans, alfalfa, wheat and cotton (Liljesthröm et al, 2002;Beltramo et al, 2006;Armendano & González, 2009Almada et al, 2012, respectively), where Anyphaenidae, Salticidae and Linyphiidae were the main families in terms of their abundance. These families are also represented with greater abundance in livestock systems (Toti et al, 2000;Warui et al, 2005), as well as in reserves and national parks (Corronca & Abdala, 1994;Rubio et al, 2004;Grismado, 2007;Avalos et al, 2009;Rubio, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…The results showed that the communities of spiders in the North of Santa Fe are affected by the design of fields within agropastoral systems. The araneofauna registered in the studied area represents 43% of the total number of families cited in Argentina (World Spider Catalog, 2016), and the richness of collected species exceeds the values known to the province of Santa Fe in soybean crops (Beltramo et al, 2006) and cotton (Almada et al, 2012) and to that of other regions or other crops studied in the country (Liljesthröm et al, 2002;Armendano & González, 2009;Benamú Pino, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Asimismo, la riqueza específica obtenida en esta investigación no difiere a las observadas en otros estudios realizados en selvas tropicales amazónicas (Höfer, 1990;Raizer et al, 2005;Machado Pinto-Leite et al, 2008;Ricetti & Bonaldo, 2008;Bonaldo & Dias, 2010;Carvalho & Avelino, 2010). Aunque en un marco menos comparable, en Argentina existen estudios sobre ecología de comunidades de arañas en agroecosistemas que revelaron niveles de riqueza más bajos, debido sin duda a la pérdida de la heterogeneidad del paisaje: cultivos de soja (Liljesthrom et al, 2002;Beltramo et al, 2006), y alfalfa (Armendano & González, 2010).…”
Section: Discusión Y Conclusionesunclassified
“…Los estudios sobre arañas exclusivamente en Argentina se enfocaron, en su mayoría, en aspectos taxonómicos y sistemáticos de algunas familias; siendo los trabajos de diversidad principalmente orientados en agroecosistemas con distintos manejos (Liljesthröm et al, 2002;Beltramo et al, 2006;Armendano & González, 2010;Avalos et al, 2013), muy pocos en áreas naturales protegidas (Rubio et al, 2008;Rubio & Moreno, 2010) o en ambientes degradados (Avalos et al, 2007). Aún hay mucho por conocer sobre la fauna nativa de arañas en Argentina, y en especial en áreas con un valor agregado (como las yungas) debido a la diversidad ambiental y biológica y al incremento de la pérdida de muchos de sus hábitats.…”
Section: Introductionunclassified
“…As a typical megadiverse group, spiders have gained wide acceptance in ecological studies as indicators of environmental quality (Clausen 1986;Maelfait et al 1990;Churchill 1997). In Argentina, research on ecological aspects of communities of spiders associated with natural (Corronca and Abdala 1994;Ávalos et al 2005;Grismado 2007;Rubio et al 2008;Ferretti et al 2010a) and altered areas (Beltramo et al 2006;Ávalos et al 2007;Armendano and González 2010) has been conducted, but knowledge gaps still exist for most of the natural areas. Moreover, there is no data on ecological aspects of the spider community in the Ventania system.…”
Section: Introductionmentioning
confidence: 99%